Revolutionizing Distance Measurement with Arduino Nano: Merevolusi Pengukuran Jarak dengan Arduino Nano - Hasyim, Mochamad; Ahfas , Akhmad (Indonesian Journal of Innovation Studies, 2024)
This study addresses the need for a practical, fast, and accurate digital meter by developing an Arduino Nano-based infrared laser distance sensor. Using the Research and Development (R&D) method, the system was designed with block diagrams, flowcharts, hardware layouts, and software programming. The device can measure distances from 5 cm to 55 meters and accurately assess non-transparent objects. However, it struggles with transparent objects and bright light sources. These results demonstrate the meter's efficiency and suggest areas for further improvement. Highlight: Measurement Range: Measures distances from 5 cm to 55 meters. Accuracy Limitations: Struggles with transparent objects and bright lights. Efficiency: Accelerates measurement process and displays results digitally. Keywoard: Digital meter, Arduino Nano, Infrared sensor, Distance Measurement, Laser technology